CARTILHA EDUCATIVA SOBRE ACIDENTES DOMÉSTICOS NA INFÂNCIA PARA AGENTES COMUNITÁRIOS DE SAÚDE - Flôres, Maria Isabel Quadros da Silveira (2022)
To build a booklet on domestic accidents in childhood for community health agents and to investigate the scientific evidence on domestic accidents in childhood. Method: For the elaboration of the educational booklet, the following steps were considered: situational diagnosis, literature review for the selection, creation and organization of content and evaluation. Regarding scientific research, it is configured as an integrative literature review, where six stages were covered: identification of the proposed theme and the research question; Choice of inclusion and exclusion criteria; selection of databases and studies; evaluation of the studies that were extracted; narration of the results and presentation of the knowledge obtained in the research. The search was performed in November 2022 in the Literatura Latino-Americana e do Caribe em Ciências da Saúde, Scientific Electronic Library Online and US National Library of Medicine PubMed library. For each database, different combinations of descriptors or Mesh Terms were used. The inclusion criteria for the study were: complete articles, with free access, in Portuguese, English and Spanish. As exclusion criteria: theses, dissertations, ministerial manuals and productions that were not in accordance with the objective. The time frame used for selecting articles in the databases was from 2017 to 2021. The analysis corpus consisted of 21 articles. Results: To develop the first objective, it was reported to community health agents the construction process of an educational booklet on domestic accidents in childhood. The process and elaboration of the technological product occurred in stages, from identifying the main types of domestic accidents in the literature, the profile of the children and the risk factors involved, selection of scientific material and elaboration of the layout and text to appear in the booklet. Afterwards, the booklet was presented and evaluated by community health agents regarding content and layout. Regarding the second objective, the scientific evidence from the articles included in the sample point out that most domestic accidents are caused by falls, occur predominantly in male children, summer as the season of the year with the highest occurrence of these accidents and the afternoon as the most prevalent period of the day. A common risk factor for falls, burns, cuts and traumatic brain injury was evidenced as being a mother with low education. Conclusions: Although we still have a considerable number of accidents involving children, and that prevention measures at home are not always addressed with families, this technology helps to guide home visits and draw the attention of Community Health Agents with guidelines directed to each room of the house. This material can also be used by the child’s guardians since it is easily accessible, succinct, clear, attractive and easy to understand. Product and its applicability: The product generated through this dissertation is a booklet entitled Safe Child in the Domestic Environment, which was developed to prevent domestic accidents in childhood and which guides the practices of Community Health Agents. Thus, the applicability of the booklet will guide the practices of preventing domestic accidents with children, through this simple, practical and easily accessible technological resource that can contribute in a promising and intuitive way to the achievement of best practices in the field of domestic accidents in childhood in the context of Primary Health Care.